Case report: Management of pediatric gigantism caused by the TADopathy, X-linked acrogigantism - Caruso, Manuela; Mazzatenta, Diego; Asioli, Sofia; Costanza, Giuseppe; Trivellin, Giampaolo; Franke, Martin; Abboud, Dayana; Hanson, Julien; Raverot, Véronique; Pétrossians, Patrick; Beckers, Albert; Cappa, Marco; et al. (Frontiers in Endocrinology, 2024)
X-linked acrogigantism (X-LAG) is a rare form of pituitary gigantism that is associated with growth hormone (GH) and prolactin-secreting pituitary adenomas/pituitary neuroendocrine tumors (PitNETs) that develop in infancy. It is caused by a duplication on chromosome Xq26.3 that leads to misexpression of the gene GPR101, a constitutively-active stimulator of pituitary GH and prolactin secretion. GPR101 normally exists within its own topologically associating domain (TAD) and is insulated from surrounding regulatory elements. X-LAG is a TADopathy in which the duplication disrupts a conserved TAD border, leading to a neoTAD in which ectopic enhancers drive GPR101 over-expression causing gigantism. Here we trace the full diagnostic and therapeutic pathway of a female patient with X-LAG from 4C-seq studies demonstrating the neoTAD through to medical and surgical interventions and detailed tumor histopathology. The complex nature of treating young children with X-LAG is illustrated, including the achievement of hormonal control using a combination of neurosurgery and adult doses of first-generation somatostatin analogs.